Risk Factors for Healthcare Associated Sepsis in Very Low Birth Weight Infants - Pereira, Helena (2016)
Introduction: Healthcare associated infections in very low birth weight infants are associated with significant morbidity and mortality and are also a cause of increased length of stay and hospital costs. The objective of this study was to evaluate the rate of healthcare-associated sepsis and associated risk factors in very low birth weight infants.Material and Methods: Retrospective observational study including very low birth weight infants hospitalized in a Neonatal Intensive Care Unit during ten years (2005-2014). We evaluated the association between several risk factors and healthcare-associated sepsis.Results: 461 very low birth weight infants were admitted. There were 110 episodes of HS in 104 very low birth weight infants and 53 episodes of sepsis associated with central vascular catheter. The density of the sepsis was 7.5/1 000 days of hospitalization and the density of central vascular catheter - associated sepsis was 22.6/1 000 days of use. The infants with HS had lower average birth weight and gestational age (959 ± 228 g vs 1191 ± 249 g and 27.6 ± 2 vs 29.8 ± 2.2 weeks), p < 0.001. After adjusting for birth weight and gestational age we verified an association between healthcare-associated sepsis and antibiotic therapy in D1, the duration of parenteral nutrition and central vascular catheter. After logistic regression only the gestational age and duration of parenteral nutrition remained as independent significant risk factors for healthcare-associated sepsis. Discussion: The independent factors for healthcare-associated sepsis are gestational age and duration of parenteral nutrition.Conclusion: For each extra week on gestational age the risk declined in 20% and for each day of NP the risk increased 22%.